COMBINED TRAUMA OF THE ALVEOLAR PROCESS AND TEETH OF THE UPPER JAW (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Injuries to teeth and alveolar processes of the jaws are among the most common types of traumatic injuries encountered in their clinical practice by dentists working with both children and adults. The upper jaw is most often subject to traumatic injuries in the anterior region due to the peculiarities of the anatomical structure of the face. Dentoalveolar anomalies increase the likelihood of injury to the anterior upper teeth (lack of anatomical splinting of the dentition and local concentration of impact load in case of dental dystopia). According to various literary sources, this type of injury accounts for 1.5 to 3.9% of the total number of injuries to the maxillofacial region [2–5].